2003
DOI: 10.1046/j.1525-1403.2003.03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Tip Granuloma Associated with Sacral Region Intrathecal Drug Administration

Abstract: Spinal cord compression from catheter tip granulomatous masses following intrathecal drug administration may produce devastating permanent neurologic deficits. Some authors have advocated intrathecal catheter placement below the conus medullaris to avoid the possibility of spinal cord involvement. Multiple cases of catheter tip granulomas in the thoracolumbar region have been reported. We present a unique case of a sacral region catheter tip inflammatory mass producing permanent neurologic deficits. A 71-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several data‐driven reports and editorial opinion, including the published guidelines of the 2002 Polyanalgesia Consensus Conference (5), have called for IT catheter placement to be below the conus medullaris to prevent the severe and sometimes permanent neurologic sequelae associated with catheter‐tip inflammatory masses (23). However, evidence from case reports suggests that implantation of IT catheters tips located at or below the conus medullaris does not necessarily remove all risk of neurologic injury that can result from inflammatory granulomas.…”
Section: The Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Several data‐driven reports and editorial opinion, including the published guidelines of the 2002 Polyanalgesia Consensus Conference (5), have called for IT catheter placement to be below the conus medullaris to prevent the severe and sometimes permanent neurologic sequelae associated with catheter‐tip inflammatory masses (23). However, evidence from case reports suggests that implantation of IT catheters tips located at or below the conus medullaris does not necessarily remove all risk of neurologic injury that can result from inflammatory granulomas.…”
Section: The Clinical Datamentioning
confidence: 99%
“…In another unique case study, an intradural extra‐axial mass was detected in the sacral region in a 71‐year‐old white male patient implanted with an IT pump for opioid treatment of failed back surgery syndrome (23). The patient experienced some postoperative pain relief but presented with progressive saddle anesthesia and bowel/bladder incontinence three years after undergoing implantation.…”
Section: The Clinical Datamentioning
confidence: 99%
“…14,21,23,24,31,35,36,79 There were case reports of traumatic syrinx owing to penetration of the spinal cord by the intrathecal 29 There was a report of withdrawal symptoms due to catheter disconnection from the pump. 28…”
Section: Complicationsmentioning
confidence: 99%
“…Such a case has been reported that required emergent sacral laminectomy with partial resection of an intradural extra‐axial mass. Unfortunately, this patient had no restoration of neurologic function (Fernandez et al, 2003).…”
Section: Signs and Symptomsmentioning
confidence: 94%